Respuesta :

Hi there!

To simplify this equation we first need to distribute.

(3)(4x) + (3)(6) + - 9x
= 12x +18 + - 9x

Next, combine like terms.

= 12x + 18 + - 9x
= (12x + - 9x) + (18)
= 3x + 18

In simplified form, 3 (4x + 6) - 9x is 3x + 18.

Hope this helps!

answer : 12x + 18 - 9x

step by step equation

first thing you want to do is  3 x 4x = 12x

the second thing you want to do is  3 x 6 = 18

the third thing you want to do is keep the 9x the same because it isn't in the parentheses therefore isn't getting affected by the 3 in the very front

the fourth thing you do is add them all up to get your answer: 12x + 18 - 9x !

i hope this helped and i hope you have a great day :) !!